Relación de la habilidad semántica y la comprensión lectora en niños y niñas de cinco años de la Institución Educativa Nº 314 del sector Rupacucha del distrito de Rioja en el año 2010 - Ruiz Pérez, Cindy (2011)
This pose investigation to determine the relationship of semantic skills and reading comprehension in children five years of School No. 314 of Rupacucha sector district Rioja in 2010. is has been considered a group of children 5 years, one educational institution by accidental sampling, according to the classification of Danhke, quoted by Hernández, Fernández and Baptista (2003), belongs to the type of correlational research with a predictive level. According to Hernandez, Fernandez and Baptista (2003), by trying to relate the semantic ability with reading comprehension, with correlational estranseccional research design, taking data at one time, in a single time concluding that the semantic skill is the ability to grant a meaning to a set word and it is necessary that the child has experiences with the outside world and while an adult help guide you with the proper lexicon to the elements already established their environment.